(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Natural disasters in recent years have shown that people are vulnerable to natural disasters and it is very difficult to protect people from natural disasters. Every year, tens of thousands of people die in various disasters and other similar emergencies. The need for the use of modern technologies and devices in emergencies is growing day by day. A variety of modern devices, techniques, and methods are used in emergencies and post-disaster search and rescue operations. Finding a survivor is a very important issue in post-disaster operations. People’s vital signs are very important in determining people’s lives. Heart rate (HR), blood pressure (BP), respiratory rate (respiratory rate), and body temperature (BT) are four important vital signs that need to be measured regularly. Various technologies are used to transmit data over long distances from sensors that measure human vital signs. One such technology is Long Range (LoRa). Long-distance transmission of human vital signs data based on Long Range (LoRa) allows monitoring a person’s location in emergencies as well as their health status.In this paper, we develop a health monitoring and emergency alarm device (beeper) based on Long Range (LoRa) that can monitor human vital signs, generate an emergency alarm when human health status is deteriorating and also transmit human vital signs data to web server/ mobile app.